PERAN ORGANISASI IKATAN DIFABEL ENREKANG INKLUSI DALAM PEMBERDAYAAN PENYANDANG DIFABEL DI KELURAHAN LAKAWAN KECAMATAN ANGGERAJA KABUPATEN ENREKANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
This journal aims to describe the form of organizational empowerment of the Enrekang Inclusion Disabled Association in empowering people with disabilities in Lakawan Village, Anggeraja District, Enrekang Regency, and how the results of the Enrekang Inclusion Disabled Association organizational empowerment in empowering persons with disabilities in Lakawan Village, Anggeraja District, Enrekang Regency. In the explanation of this journal, this type of research is qualitative research that uses a community development approach, especially from the aspect of increasing the capacity of people with disabilities and various series of activities such as observation, interviews, and documentation. At the same time, the data analysis used is data reduction, data presentation, and conclusion. The results of this study indicate that there are six forms of empowerment of the Enrekang Inclusion Disabled Association: (1) Independent and mental training, (2) Sign language training, (3) Skills training, (4) Accompanying assistance, (5) Gathering, (6) Assistance venture capital. The results of empowering people with the Enrekang Inclusion Disabled Association: (1) Self-acceptance, (2) Community recognition, (3) Special health insurance, (4) Economic improvement, (5) Government social support.